Preparation process of high-performance composite porcelain suspension rod insulator
By coating and vulcanizing modified silicone rubber on the surface of the porcelain column, the problem of poor weather resistance of traditional porcelain suspended rod insulators in harsh environments is solved, and the preparation of high-performance composite porcelain suspended rod insulators is realized, which improves its mechanical strength and electrical properties.
Patent Information
- Application Number
- CN202510043110.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Traditional porcelain suspended rod insulators have poor weather resistance in harsh environments and are prone to aging and cracking, affecting their service life and electrical properties.
The high-performance composite porcelain suspended rod insulator is used to improve the mechanical strength and weather resistance of the insulator by coating and vulcanizing the modified silicone rubber on the surface of the roughened porcelain column, combining the advantages of the porcelain column and the modified silicone rubber.
It significantly improves the weather resistance, electrical insulation performance and mechanical strength of composite porcelain suspended rod insulators, reduces discharge phenomena caused by filth, and extends the service life of the insulators.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating materials, and in particular to a preparation process of a high-performance composite porcelain suspension rod insulator. Background Art
[0002] In the power transmission system, suspension insulators are key components that bear the important responsibility of isolating the conductor from the ground and preventing current leakage. Traditionally, suspension insulators are mostly made of a single porcelain material. Although this material has good electrical insulation performance and mechanical strength, it has poor weather resistance in harsh environments (such as high temperature, humidity, dirt, etc.), and is prone to aging, cracking and other problems, which affects its service life and electrical performance.
[0003] In order to overcome the shortcomings of traditional porcelain suspension rod insulators, the industry has begun to explore the use of composite materials to prepare insulators. Among them, composite porcelain suspension rod insulators, as a new type of material, combine the excellent electrical insulation properties of porcelain materials with the weather resistance and anti-aging properties of composite materials, and have gradually become a research hotspot. However, the preparation process of composite porcelain suspension rod insulators still faces many challenges, especially in the treatment of the surface of the porcelain column. How to form a protective layer that can protect the porcelain column from environmental erosion and maintain good electrical insulation performance is an urgent problem to be solved.
[0004] Chinese patent document CN106243859A discloses an anti-pollution flashover insulator, including an insulator body and a coating coated on the surface of the body, wherein the coating is a nano-fluorocarbon coating, and the nano-fluorocarbon coating includes the following components by mass percentage: 5-10% nano-silicon dioxide, 5-10% cross-linking agent, 8-14% organic metal compound, and the rest is fluorocarbon coating. The inner and outer surfaces of the anti-pollution flashover insulator provided by the invention are all covered with a nano-fluorocarbon coating; because the nano-fluorocarbon coating has good film-forming properties, strong covering power and hardness, and strong and reliable bonding properties, the anti-pollution flashover insulator of the invention has excellent hydrophobicity, mechanical properties, pollution resistance and ice melting properties, significantly reducing the probability of pollution flashover and ensuring the safe operation of the power grid. The nano-silicon dioxide used in the invention is a nano-compound, and there is a defect of easy agglomeration in the coating matrix, resulting in poor mechanical properties of the coating, which in turn affects the safety of the insulator during use. Summary of the invention
[0005] The main purpose of the present invention is to propose a preparation process for a high-performance composite porcelain suspension rod insulator, in which modified silicone rubber is coated and vulcanized on the surface of a roughened porcelain column, which combines the advantages of the porcelain column and the modified silicone rubber, improves the mechanical strength of the composite insulator, and enables it to withstand a greater mechanical load; improves the weather resistance of the porcelain insulator to prevent performance degradation in harsh environments; improves the anti-pollution flashover performance of the porcelain insulator, and reduces discharge phenomena caused by contamination.
[0006] To achieve the above-mentioned purpose, the present invention proposes a high-performance composite porcelain suspension rod insulator, comprising a porcelain column insulator body and a modified silicone rubber coated on the surface of the porcelain column insulator body; the porcelain column insulator body comprises the following components in parts by mass: 10-25 parts of Qingyuan mud, 10-20 parts of ash clay, 8-15 parts of kiln mud, 15-25 parts of porcelain clay, 5-20 parts of bauxite, 5-15 parts of nano silicon carbide, 3-10 parts of quartz sand, 10-15 parts of modified epoxy resin, and 5-8 parts of curing agent.
[0007] Preferably, the preparation method of the modified epoxy resin is as follows:
[0008] The carbon fiber is plasma treated and then immersed in a sodium hydroxide aqueous solution, and then taken out and dried to obtain a pretreated carbon fiber; the carboxyl-terminated perfluoropolyether is dissolved in N,N-dimethylformamide, 4-amino-3-hydroxybenzoic acid and EDC / NHS aqueous solution are added, the pH is adjusted to 4-6, heated for reaction, and the pretreated carbon fiber is immersed in the reaction solution after cooling. After the impregnation is completed, the carbon fiber is taken out, dried, crushed and sieved to obtain a polymer-coated carbon fiber; the polymer-coated carbon fiber is added to the epoxy resin and stirred to mix evenly to obtain the modified epoxy resin.
[0009] Preferably, the mass ratio of the carboxyl-terminated perfluoropolyether, 4-amino-3-hydroxybenzoic acid, and pretreated carbon fiber is 100:8-10:6-10; the concentration of EDC in the EDC / NHS aqueous solution is 30-40mM / L, and the concentration of NHS is 40-50mM / L; the mass ratio of the polymer-coated carbon fiber and the epoxy resin is 10-15:50-70.
[0010] The modified epoxy resin used in the present invention is obtained by toughening and modifying the epoxy resin by coating the carbon fiber with a polymer. The preparation method thereof comprises the following steps: firstly, the carbon fiber is treated with plasma to form surface micropits on the fiber surface, thereby increasing the surface roughness of the fiber and facilitating improving the bonding strength between the carbon fiber and the polymer; and then, the functional groups on the surface of the carbon fiber can be activated by treating the carbon fiber with an alkali, thereby further improving the bonding strength between the carbon fiber and the polymer; then, the carboxyl-terminated perfluoropolyether and 4-amino-3-hydroxybenzoic acid react under the action of a carboxyl activator EDC / NHS; the addition of 4-amino-3-hydroxybenzoic acid can introduce active hydroxyl groups and carboxyl groups into the polymer molecules, thereby enhancing the interface bonding force between the modified epoxy resin and the natural mineral raw material; and on the other hand, the carboxyl-terminated perfluoropolyether is an elastomer with lubricating properties, and the introduction of the carboxyl-terminated perfluoropolyether into the epoxy resin can synergistically improve the toughness and impact resistance of the epoxy resin with the carbon fiber, thereby improving the mechanical properties of the epoxy resin, and further improving the mechanical properties of the porcelain column insulator body.
[0011] Preferably, the curing agent is a polyamide curing agent and / or an acid anhydride curing agent.
[0012] Preferably, the method for preparing the high-performance composite porcelain suspension rod insulator comprises the following steps:
[0013] S1. Weigh the raw materials according to the formula, mix Qingyuan mud, ash clay, kiln mud, porcelain clay and bauxite evenly, and then put them into a ball mill to obtain a mixture;
[0014] S2, wet ball milling: adding nano silicon carbide, quartz sand, and modified epoxy resin to the mixture obtained in step S1 to obtain a mixed material, adding water to perform wet ball milling to obtain a slurry; then adding a curing agent and mixing and stirring to obtain a base material;
[0015] S3, green compacting: adding the base material obtained in step S2 into a mold for molding, degassing, heating and curing, cooling and demolding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body;
[0016] S4, preparing modified silicone rubber: putting the raw silicone rubber into a kneader, adding a structure control agent, a filler, an anti-aging agent, and an accelerator for mixing, and then adding a vulcanizing agent, thinning, and producing a sheet to obtain the modified silicone rubber;
[0017] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0018] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding to obtain a high-performance composite porcelain suspension rod insulator.
[0019] Preferably, the particle size of the mixture in step S1 is 50-200 mesh.
[0020] Preferably, the amount of water added in step S2 is 5-10% of the mass of the mixture.
[0021] Preferably, the degassing process conditions in step S3 are: first degassing at 25-35° C. for 1-2 h under vacuum conditions, and then degassing at 50-60° C. for 0.5-1 h.
[0022] Preferably, the heating and curing conditions in step S3 are first curing at 70-80° C. for 4-5 hours, and then curing at 130-140° C. for 4-5 hours.
[0023] Preferably, in step S4, the structure control agent is hydroxy silicone oil and / or diphenylsilanediol; the filler is at least one of white carbon black, aluminum hydroxide, modified nano titanium dioxide, and alumina fiber; the accelerator is triethanolamine; the antioxidant is a phenol antioxidant; and the vulcanizing agent is at least one of diisopropylbenzene peroxide, sulfur, and sodium isobutyl xanthate.
[0024] Preferably, the preparation process of the modified silicone rubber in step S4 is as follows: put methyl vinyl silicone rubber into a kneader, add white carbon black, aluminum hydroxide, hydroxy silicone oil, diphenylsilanediol, and triethanolamine, mix evenly, add modified nano titanium dioxide, alumina fiber, and 4-methyl-6-tert-butylphenol, heat to 130-150°C, knead for 1-2 hours at -0.1MPa to -0.08MPa, and discharge the material. The obtained rubber material is put into an open mill, and the mixture is kneaded to a smooth rubber material, and the mixture is allowed to stand for 18-24 hours. The mixture is rolled on the open mill, a vulcanizing agent is added, and thinned 5-10 times, a sheet is produced, and the modified silicone rubber is obtained after standing for 18-24 hours.
[0025] Preferably, in step S4, the mass ratio of methyl vinyl silicone rubber, white carbon black, aluminum hydroxide, hydroxy silicone oil, diphenylsilanediol, triethanolamine, modified nano titanium dioxide, alumina fiber, 4-methyl-6-tert-butylphenol, and vulcanizing agent is 70-90:20-30:30-35:3-5:0.5-1:0.5-1:15-25:10-20:0.5-1:1-2.
[0027] Preferably, the preparation method of the modified titanium dioxide in step S4 is as follows:
[0028] The nano titanium dioxide is added to an ethanol aqueous solution, KH550 is added, and the reaction is heated. After the reaction is completed, the reaction is cooled and filtered. After the solid is collected and washed, it is added to dimethyl sulfoxide, NaOH is added to adjust the pH value to 8-10, 5-amino-2-fluorobenzyl alcohol is added, and the reaction is heated. After the reaction is completed, the reaction is cooled, filtered, and washed until the pH value of the filtrate is neutral, and then dried to obtain fluorinated titanium dioxide; the fluorinated titanium dioxide is dispersed in water, glycidyl trimethylammonium chloride is added, and the reaction is heated. After the reaction is completed, the reaction is cooled, the solid is collected by filtration, washed, and dried to obtain modified nano titanium dioxide.
[0029] Preferably, the mass ratio of the nano titanium dioxide, KH550, 5-amino-2-fluorobenzyl alcohol and glycidyltrimethylammonium chloride is 15-25:2-3:4-6:3-5.
[0030] Nano-titanium dioxide is a material with self-cleaning function. It can decompose organic pollutants under light conditions. By modifying it, its compatibility with the modified silicone rubber system can be significantly improved, so that it forms a dense, interwoven three-dimensional network structure in the modified silicone rubber matrix. This dense network can not only improve the dispersion of the filler, but also form physical cross-linking points, enhance the mechanical properties and thermal stability of the modified silicone rubber, and destroy organic microorganisms, making algae spores lose their reproductive ability, thereby inhibiting the growth of algae. It has a long service life and is durable and long-lasting in its anti-algae properties. At the same time, it improves the adhesion and accumulation of dirt on the surface of the modified silicone rubber and improves the anti-fouling flash property of the modified silicone rubber.
[0031] The preparation of the modified titanium dioxide first introduces amino groups on its surface, then reacts the amino groups with titanium dioxide and 5-amino-2-fluorobenzyl alcohol to obtain fluorinated modified titanium dioxide, and finally reacts the amino groups on the fluorinated modified titanium dioxide with the epoxy groups in the fluorinated modified titanium dioxide. By introducing the fluorine element on the modified titanium dioxide, the antifouling performance of the modified titanium dioxide is improved; by grafting glycidyltrimethylammonium chloride on the surface of the modified titanium dioxide, the growth and reproduction of bacteria and algae can be inhibited, and microbial contamination can be reduced, which is beneficial to reducing the formation of pollutants such as algae on the surface of the insulator, thereby maintaining good insulation performance, reducing discharge phenomena caused by contamination, and ensuring the reliability and safety of the power transmission system.
[0032] Preferably, the coating method in step S5 is one of spraying, brushing and dipping.
[0033] Preferably, the vulcanization molding process in the S6 step is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 100-140°C and a vulcanization time of 3-20min; the process parameters of the secondary vulcanization are a vulcanization temperature of 150-200°C and a secondary vulcanization time of 5-20min; the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 0.5-2mm.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The high-performance composite porcelain suspension rod insulator of the present invention significantly improves the weather resistance, electrical insulation performance and mechanical strength of the composite porcelain suspension rod insulator by introducing vulcanized composite silicone rubber as a protective layer of the porcelain column; the vulcanized modified silicone rubber has excellent aging resistance, weather resistance and electrical insulation performance, and can effectively resist the erosion of the insulator by harsh environment;
[0036] 2. Roughen the surface of the porcelain column to increase the adhesion of the vulcanized modified silicone rubber coating. At the same time, the coating method of the vulcanized modified silicone rubber is spraying, brushing or dipping to ensure that the coating is uniform and the thickness is controllable. The firm combination of the modified silicone rubber and the surface of the porcelain column ensures the long-term stable operation of the insulator;
[0037] 3. The present invention improves the mechanical properties of epoxy resin by modifying the epoxy resin, thereby improving the mechanical properties of the porcelain column insulator body; by adding modified nano-titanium dioxide to the modified silicone rubber coating, a relatively dense filler network structure can be formed in the modified silicone rubber coating to enhance the filling effect, thereby improving the mechanical properties and anti-fouling properties of the modified silicone rubber coating; at the same time, the adhesion and accumulation of surface dirt and algae and other organisms on the modified silicone rubber are improved, the anti-fouling flashover of the modified silicone rubber is improved, the discharge phenomenon caused by dirt is reduced, and the service life of the high-performance composite porcelain suspension rod insulator is increased. DETAILED DESCRIPTION
[0038] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0039] The sources of some raw materials used in the present invention are as follows:
[0040] Carboxyl-terminated perfluoropolyether, molecular weight 3000, was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0041] Epoxy resin, E44, content of 99%, was purchased from Yunsheng Chemical (Shandong) Co., Ltd.
[0042] Polyamide curing agent, model 650, was purchased from Zhengzhou Huipeng Chemical Products Co., Ltd.
[0043] Nano-silicon carbide, with an average particle size of 0.5 μm, was purchased from Hangzhou Jikang New Materials Co., Ltd.
[0044] Methyl vinyl silicone rubber, vinyl content 1.8-5%, was purchased from Dongguan Bailing New Materials Co., Ltd.
[0045] White carbon black, 300 mesh, Shanghai Yuanjiang Chemical Co., Ltd.
[0046] Aluminum hydroxide, with a particle size of 5-100 μm, was purchased from Shandong Feishuo Chemical Technology Co., Ltd.
[0047] Nano-titanium dioxide, rutile type, particle size 30 nm, was purchased from Shanghai Yingcheng New Materials Co., Ltd.
[0048] Example 1
[0049] A method for preparing a high-performance composite porcelain suspension rod insulator comprises the following steps:
[0050] S1, 400g Qingyuan mud, 300g ash clay, 240g kiln mud, 400g porcelain clay, 300g bauxite were mixed evenly and put into a ball mill to obtain a mixture of 50-200 mesh;
[0051] S2, wet ball milling: 200g of nano silicon carbide, 120g of quartz sand, and 240g of modified epoxy resin are added to the mixture obtained in step S1 to obtain a mixed material, and water is added for wet ball milling, wherein the amount of water added is 8% of the mass of the mixed material to obtain a slurry; then 130g of polyamide 650 curing agent is added and mixed and stirred to obtain a base material;
[0052] S3, green compacting: adding the base material obtained in step S2 into a mold for compression molding, degassing, heating and curing, cooling and demolding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; the degassing process conditions are: degassing at 30°C for 2h under vacuum conditions, and then degassing at 55°C for 0.5h; the heating and curing conditions are: curing at 80°C for 4h, and then curing at 130°C for 5h;
[0053] S4, preparation of modified silicone rubber: 160g of methyl vinyl silicone rubber was put into a kneader, 50g of white carbon black, 64g of aluminum hydroxide, 8g of hydroxy silicone oil, 1.2g of diphenylsilanediol, and 1.4g of triethanolamine were added, and after mixing evenly, 40g of modified nano titanium dioxide, 30g of alumina fiber, and 1.6g of 4-methyl-6-tert-butylphenol were added, and the temperature was raised to 140°C, and the material was kneaded at -0.1MPa for 1h and discharged. The obtained rubber material was put into an open mill, and the rubber material was mixed until the rubber material was smooth, and the mixture was allowed to stand for 18h. The mixture was rolled on the open mill, 3g of diisopropylbenzene peroxide was added, and the mixture was thinned 8 times to obtain a sheet, and the modified silicone rubber was obtained after standing for 20h;
[0054] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0055] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding, the vulcanization molding process is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 120°C and a vulcanization time of 10 min; the process parameters of the secondary vulcanization are a vulcanization temperature of 180°C and a secondary vulcanization time of 10 min, the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 1 mm; a high-performance composite porcelain suspension rod insulator is obtained.
[0056] The preparation method of the modified epoxy resin in step S2 is as follows:
[0057] 20g of carbon fiber was treated with plasma and then immersed in 200mL of 1mol / L sodium hydroxide aqueous solution. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen, the power was set to 180W, and the treatment time was 8min; the immersion time was 2h, and after the immersion was completed, the carbon fiber was taken out, washed and dried to obtain the pretreated carbon fiber; 100g of carboxyl-terminated perfluoropolyether was dissolved in 500mL of N,N-dimethylformamide, 10g of 5-amino-2-fluorobenzyl alcohol and 100mL of EDC / NHS aqueous solution (the concentration of EDC in the EDC / NHS aqueous solution was 40mM / L, and the concentration of NHS was 50mM / L) were added, the pH was adjusted to 5, and the reaction was heated at 60°C for 3h. After cooling, 8g of the pretreated carbon fiber was immersed in the reaction solution, and after immersion for 1h, the carbon fiber was taken out, dried, and crushed through a 120-mesh sieve to obtain the polymer-coated carbon fiber; 12g of the polymer-coated carbon fiber was added to 65g of epoxy resin and stirred and mixed evenly to obtain the modified epoxy resin.
[0058] The preparation method of the modified titanium dioxide in step S4 is as follows:
[0059] 20 g of nano titanium dioxide was added to 200 mL of 50 wt% ethanol aqueous solution, 2.5 g of KH550 was added, and the mixture was heated at 50° C. for 4 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected and washed, it was added to 200 mL of dimethyl sulfoxide. A 1 mol / L NaOH aqueous solution was added to adjust the pH value to 9. 5.2 g of 5-amino-2-fluorobenzyl alcohol was added, and the mixture was heated at 60° C. for 2 h. After the reaction was completed, the mixture was cooled, filtered, and washed until the pH value of the filtrate was neutral, and then dried to obtain fluorinated titanium dioxide. The fluorinated titanium dioxide was dispersed in 200 mL of water, 4.5 g of glycidyltrimethylammonium chloride was added, and the mixture was heated at 60° C. for 4 h. After the reaction was completed, the mixture was cooled, filtered, collected, washed, and dried to obtain modified nano titanium dioxide.
[0060] After testing, the high-performance composite porcelain suspension rod insulator prepared in this embodiment has an anti-algae property of level 2.
[0061] Example 2
[0062] A method for preparing a high-performance composite porcelain suspension rod insulator comprises the following steps:
[0063] S1, 200g Qingyuan mud, 200g ash clay, 160g kiln mud, 300g porcelain clay, 100g bauxite were mixed evenly and put into a ball mill to obtain a mixture of 50-200 mesh;
[0064] S2, wet ball milling: 100g of nano silicon carbide, 60g of quartz sand, and 200g of modified epoxy resin are added to the mixture obtained in step S1 to obtain a mixed material, and water is added for wet ball milling, wherein the amount of water added is 5% of the mass of the mixed material to obtain a slurry; then 100g of polyamide 650 curing agent is added, and the mixture is mixed and stirred evenly to obtain a base material;
[0065] S3, green compacting: adding the base material obtained in step S2 into a mold for compression molding, degassing, heating and curing, cooling and demoulding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; the degassing process conditions are: degassing at 25°C for 1 hour under vacuum conditions, and then degassing at 50°C for 1 hour; the heating and curing conditions are: curing at 70°C for 5 hours, and then curing at 140°C for 4 hours;
[0066] S4, preparation of modified silicone rubber: 140g of methyl vinyl silicone rubber was put into a kneader, 40g of white carbon black, 60g of aluminum hydroxide, 6g of hydroxy silicone oil, 1g of diphenylsilanediol, and 1g of triethanolamine were added, and after mixing evenly, 30g of modified nano titanium dioxide, 20g of alumina fiber, and 1g of 4-methyl-6-tert-butylphenol were added, and the temperature was raised to 130°C, and the material was kneaded at -0.08MPa for 2h and discharged. The obtained rubber material was put into an open mill, and the rubber material was mixed to a smooth rubber, and the mixture was allowed to stand for 20h. The mixed rubber was rolled on the open mill, 2g of sodium isobutyl xanthate was added, and the mixture was thinned 5 times to obtain a sheet, and the modified silicone rubber was obtained after standing for 18h;
[0067] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0068] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding, the vulcanization molding process is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 100°C and a vulcanization time of 3 minutes; the process parameters of the secondary vulcanization are a vulcanization temperature of 150°C and a secondary vulcanization time of 5 minutes, the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 1 mm; a high-performance composite porcelain suspension rod insulator is obtained.
[0069] The preparation method of the modified epoxy resin in step S2 is as follows:
[0070] 20g of carbon fiber was plasma treated and then immersed in 200mL of 1mol / L sodium hydroxide aqueous solution. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen, the power was set to 180W, and the treatment time was 8min; the immersion time was 2h, and after the immersion was completed, the carbon fiber was taken out, washed and dried to obtain the pretreated carbon fiber; 100g of carboxyl-terminated perfluoropolyether was dissolved in 500mL of N,N-dimethylformamide, 8g of 5-amino-2-fluorobenzyl alcohol and 100mL of EDC / NHS aqueous solution (the concentration of EDC in the EDC / NHS aqueous solution was 30mM / L, and the concentration of NHS was 40mM / L) were added, the pH was adjusted to 4, and the reaction was heated at 60°C for 3h. After cooling, the pretreated carbon fiber was immersed in the reaction solution, and after immersion for 1h, the carbon fiber was taken out, dried, and crushed through a 120-mesh sieve to obtain a polymer-coated carbon fiber; 10g of the polymer-coated carbon fiber was added to 50g of epoxy resin and stirred and mixed evenly to obtain the modified epoxy resin.
[0071] The preparation method of the modified titanium dioxide in step S4 is as follows:
[0072] 15 g of nano titanium dioxide was added to 200 mL of 50 wt% ethanol aqueous solution, 2.2 g of KH550 was added, and the mixture was heated at 50° C. for 4 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected and washed, it was added to 200 mL of dimethyl sulfoxide. A 1 mol / L NaOH aqueous solution was added to adjust the pH value to 8. 4 g of 5-amino-2-fluorobenzyl alcohol was added, and the mixture was heated at 60° C. for 2 h. After the reaction was completed, the mixture was cooled, filtered, and washed until the pH value of the filtrate was neutral, and then dried to obtain fluorinated titanium dioxide. The fluorinated titanium dioxide was dispersed in 200 mL of water, 3 g of glycidyltrimethylammonium chloride was added, and the mixture was heated at 60° C. for 4 h. After the reaction was completed, the mixture was cooled, filtered, collected, washed, and dried to obtain modified nano titanium dioxide.
[0073] Example 3
[0074] A method for preparing a high-performance composite porcelain suspension rod insulator comprises the following steps:
[0075] S1, 500g Qingyuan mud, 400g ash clay, 300g kiln mud, 500g porcelain clay, 400g bauxite were mixed evenly and put into a ball mill to obtain a mixture of 50-200 mesh;
[0076] S2, wet ball milling: 300g of nano silicon carbide, 200g of quartz sand, and 300g of modified epoxy resin are added to the mixture obtained in step S1 to obtain a mixed material, and water is added for wet ball milling, wherein the amount of water added is 10% of the mass of the mixed material to obtain a slurry; then 160g of polyamide 650 curing agent is added and mixed and stirred to obtain a base material;
[0077] S3, green compacting: adding the base material obtained in step S2 into a mold, performing compression molding, degassing, heating and curing, cooling and demoulding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; the degassing process conditions are: degassing at 35°C for 1h under vacuum conditions, and then degassing at 60°C for 0.5-1h; the heating and curing conditions are: curing at 80°C for 4h, and then curing at 140°C for 5h;
[0078] S4, preparation of modified silicone rubber: 180g of methyl vinyl silicone rubber was put into a kneader, 60g of white carbon black, 70g of aluminum hydroxide, 10g of hydroxy silicone oil, 2g of diphenylsilanediol, and 2g of triethanolamine were added, and after uniform mixing, 50g of modified nano titanium dioxide, 40g of alumina fiber, and 2g of 4-methyl-6-tert-butylphenol were added, and the temperature was raised to 150°C, and the mixture was kneaded at -0.08MPa for 2h and discharged. The obtained rubber material was put into an open mill, and the mixture was mixed until the rubber material was smooth, and the mixture was allowed to stand for 24h. The mixed rubber was rolled on the open mill, 4g of sulfur was added, and the mixture was thinned 10 times to obtain a sheet, and the modified silicone rubber was obtained after standing for 24h;
[0079] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0080] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding, the vulcanization molding process is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 140°C and a vulcanization time of 20 minutes; the process parameters of the secondary vulcanization are a vulcanization temperature of 200°C and a secondary vulcanization time of 20 minutes, the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 1 mm; a high-performance composite porcelain suspension rod insulator is obtained.
[0081] The preparation method of the modified epoxy resin in step S2 is as follows:
[0082] 20g of carbon fiber was plasma treated and then immersed in 200mL of 1mol / L sodium hydroxide aqueous solution. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen, the power was set to 180W, and the treatment time was 8min; the immersion time was 2h, and after the immersion was completed, the carbon fiber was taken out, washed and dried to obtain the pretreated carbon fiber; 100g of carboxyl-terminated perfluoropolyether was dissolved in 500mL of N,N-dimethylformamide, 10g of 5-amino-2-fluorobenzyl alcohol and 100mL of EDC / NHS aqueous solution (the concentration of EDC in the EDC / NHS aqueous solution was 35mM / L, and the concentration of NHS was 45mM / L) were added, the pH was adjusted to 6, and the reaction was heated at 60°C for 3h. After cooling, the pretreated carbon fiber was immersed in the reaction solution, and after immersion for 1h, the carbon fiber was taken out, dried, and crushed through a 120-mesh sieve to obtain a polymer-coated carbon fiber; 15g of the polymer-coated carbon fiber was added to 70g of epoxy resin and stirred and mixed evenly to obtain the modified epoxy resin.
[0083] The preparation method of the modified nano titanium dioxide in step S4 is as follows: 25g of titanium dioxide is dispersed in an ethanol aqueous solution, 3g of vinyl trimethoxysilane is added, and the mixture is heated at 50°C for reaction for 4h. After the reaction is completed, the mixture is cooled and filtered, and the solid is collected, washed, and dried to obtain vinyl coupled titanium dioxide; 5g of vinyl POSS is dissolved in 150mL of chloroform, 4g of vinyl coupled titanium dioxide and 0.15g of azobisisobutyronitrile are added, and the mixture is heated at 80°C for reaction for 4h. After the reaction is completed, the mixture is cooled and filtered, and the solid is collected, washed, and dried, and then dispersed in 200mL of a 50wt% ethanol aqueous solution, 1.5g of mercaptopropylmethyldimethoxysilane is added, and the mixture is heated at 50°C for reaction for 4h. After the reaction is completed, the mixture is cooled and filtered, and the solid is collected, washed, and dried to obtain modified nano titanium dioxide.
[0084] The preparation method of the modified titanium dioxide in step S4 is as follows:
[0085] 25 g of nano titanium dioxide was added to 200 mL of 50 wt% ethanol aqueous solution, 3 g of KH550 was added, and the mixture was heated at 50° C. for 4 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected and washed, it was added to 200 mL of dimethyl sulfoxide. A 1 mol / L NaOH aqueous solution was added to adjust the pH value to 10. 6 g of 5-amino-2-fluorobenzyl alcohol was added, and the mixture was heated at 60° C. for 2 h. After the reaction was completed, the mixture was cooled, filtered, and washed until the pH value of the filtrate was neutral, and then dried to obtain fluorinated titanium dioxide. The fluorinated titanium dioxide was dispersed in 200 mL of water, 5 g of glycidyltrimethylammonium chloride was added, and the mixture was heated at 60° C. for 4 h. After the reaction was completed, the mixture was cooled, filtered, collected, washed, and dried to obtain modified nano titanium dioxide.
[0086] Comparative Example 1
[0087] A method for preparing a high-performance composite porcelain suspension rod insulator is similar to that of Example 1, except that the epoxy resin is not modified, and specifically comprises the following steps:
[0088] S1, 400g Qingyuan mud, 300g ash clay, 240g kiln mud, 400g porcelain clay, 300g bauxite were mixed evenly and put into a ball mill to obtain a mixture of 50-200 mesh;
[0089] S2, wet ball milling: 200g of nano silicon carbide, 120g of quartz sand, and 240g of epoxy resin are added to the mixture obtained in step S1 to obtain a mixed material, and water is added for wet ball milling, wherein the amount of water added is 8% of the mass of the mixed material to obtain a slurry; then 130g of polyamide 650 curing agent is added and mixed and stirred to obtain a base material;
[0090] S3, green compacting: adding the base material obtained in step S2 into a mold for compression molding, degassing, heating and curing, cooling and demolding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; the degassing process conditions are: degassing at 30°C for 2h under vacuum conditions, and then degassing at 55°C for 0.5h; the heating and curing conditions are: curing at 80°C for 4h, and then curing at 130°C for 5h;
[0091] S4, preparation of modified silicone rubber: 160g of methyl vinyl silicone rubber was put into a kneader, 50g of white carbon black, 64g of aluminum hydroxide, 8g of hydroxy silicone oil, 1.2g of diphenylsilanediol, and 1.4g of triethanolamine were added, and after mixing evenly, 40g of modified nano titanium dioxide, 30g of alumina fiber, and 1.6g of 4-methyl-6-tert-butylphenol were added, and the temperature was raised to 140°C, and the material was kneaded at -0.1MPa for 1h and discharged. The obtained rubber material was put into an open mill, and the rubber material was mixed until the rubber material was smooth, and the mixture was allowed to stand for 18h. The mixture was rolled on the open mill, 3g of diisopropylbenzene peroxide was added, and the mixture was thinned 8 times to obtain a sheet, and the modified silicone rubber was obtained after standing for 20h;
[0092] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0093] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding, the vulcanization molding process is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 120°C and a vulcanization time of 10 min; the process parameters of the secondary vulcanization are a vulcanization temperature of 180°C and a secondary vulcanization time of 10 min, the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 1 mm; a high-performance composite porcelain suspension rod insulator is obtained.
[0094] The preparation method of the modified titanium dioxide in step S4 is as follows:
[0095] 20 g of nano titanium dioxide was added to 200 mL of 50 wt% ethanol aqueous solution, 2.5 g of KH550 was added, and the mixture was heated at 50° C. for 4 h. After the reaction was completed, the mixture was cooled and filtered. After the solid was collected and washed, it was added to 200 mL of dimethyl sulfoxide. A 1 mol / L NaOH aqueous solution was added to adjust the pH value to 9. 5.2 g of 5-amino-2-fluorobenzyl alcohol was added, and the mixture was heated at 60° C. for 2 h. After the reaction was completed, the mixture was cooled, filtered, and washed until the pH value of the filtrate was neutral, and then dried to obtain fluorinated titanium dioxide. The fluorinated titanium dioxide was dispersed in 200 mL of water, 4.5 g of glycidyltrimethylammonium chloride was added, and the mixture was heated at 60° C. for 4 h. After the reaction was completed, the mixture was cooled, filtered, collected, washed, and dried to obtain modified nano titanium dioxide.
[0096] Comparative Example 2
[0097] A method for preparing a high-performance composite porcelain suspension rod insulator is similar to that of Example 1, except that the nano-titanium dioxide is not modified, and specifically comprises the following steps:
[0098] S1, 400g Qingyuan mud, 300g ash clay, 240g kiln mud, 400g porcelain clay, 300g bauxite were mixed evenly and put into a ball mill to obtain a mixture of 50-200 mesh;
[0099] S2, wet ball milling: 200g of nano silicon carbide, 120g of quartz sand, and 240g of modified epoxy resin are added to the mixture obtained in step S1 to obtain a mixed material, and water is added for wet ball milling, wherein the amount of water added is 8% of the mass of the mixed material to obtain a slurry; then 130g of polyamide 650 curing agent is added and mixed and stirred to obtain a base material;
[0100] S3, green compacting: adding the base material obtained in step S2 into a mold for compression molding, degassing, heating and curing, cooling and demolding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; the degassing process conditions are: degassing at 30°C for 2h under vacuum conditions, and then degassing at 55°C for 0.5h; the heating and curing conditions are: curing at 80°C for 4h, and then curing at 130°C for 5h;
[0101] S4, preparation of modified silicone rubber: 160g of methyl vinyl silicone rubber was put into a kneader, 50g of white carbon black, 64g of aluminum hydroxide, 8g of hydroxy silicone oil, 1.2g of diphenylsilanediol, and 1.4g of triethanolamine were added, and after mixing evenly, 40g of nano titanium dioxide, 30g of aluminum oxide fiber, and 1.6g of 4-methyl-6-tert-butylphenol were added, and the temperature was raised to 140°C, and the material was kneaded at -0.1MPa for 1h and discharged. The obtained rubber material was put into an open mill, and the rubber material was mixed until the rubber material was smooth, and the mixture was allowed to stand for 18h. The mixture was rolled on the open mill, 3g of diisopropylbenzene peroxide was added, and the mixture was thinned 8 times to obtain a sheet, and the modified silicone rubber was obtained after standing for 20h;
[0102] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0103] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding, the vulcanization molding process is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 120°C and a vulcanization time of 10 min; the process parameters of the secondary vulcanization are a vulcanization temperature of 180°C and a secondary vulcanization time of 10 min, the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 1 mm; a high-performance composite porcelain suspension rod insulator is obtained.
[0104] The preparation method of the modified epoxy resin in step S2 is as follows:
[0105] 20g of carbon fiber was treated with plasma and then immersed in 200mL of 1mol / L sodium hydroxide aqueous solution. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen, the power was set to 180W, and the treatment time was 8min; the immersion time was 2h, and after the immersion was completed, the carbon fiber was taken out, washed and dried to obtain the pretreated carbon fiber; 100g of carboxyl-terminated perfluoropolyether was dissolved in 500mL of N,N-dimethylformamide, 10g of 5-amino-2-fluorobenzyl alcohol and 100mL of EDC / NHS aqueous solution (the concentration of EDC in the EDC / NHS aqueous solution was 40mM / L, and the concentration of NHS was 50mM / L) were added, the pH was adjusted to 5, and the reaction was heated at 60°C for 3h. After cooling, 8g of the pretreated carbon fiber was immersed in the reaction solution, and after immersion for 1h, the carbon fiber was taken out, dried, and crushed through a 120-mesh sieve to obtain the polymer-coated carbon fiber; 12g of the polymer-coated carbon fiber was added to 65g of epoxy resin and stirred and mixed evenly to obtain the modified epoxy resin.
[0106] Comparative Example 3
[0107] A method for preparing a high-performance composite porcelain suspension rod insulator is similar to that of Example 1, except that the modified nano titanium dioxide is fluorinated nano titanium dioxide, and specifically comprises the following steps:
[0108] S1, 400g Qingyuan mud, 300g ash clay, 240g kiln mud, 400g porcelain clay, 300g bauxite were mixed evenly and put into a ball mill to obtain a mixture of 50-200 mesh;
[0109] S2, wet ball milling: 200g of nano silicon carbide, 120g of quartz sand, and 240g of modified epoxy resin are added to the mixture obtained in step S1 to obtain a mixed material, and water is added for wet ball milling, wherein the amount of water added is 8% of the mass of the mixed material to obtain a slurry; then 130g of polyamide 650 curing agent is added and mixed and stirred to obtain a base material;
[0110] S3, green compacting: adding the base material obtained in step S2 into a mold for compression molding, degassing, heating and curing, cooling and demolding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; the degassing process conditions are: degassing at 30°C for 2h under vacuum conditions, and then degassing at 55°C for 0.5h; the heating and curing conditions are: curing at 80°C for 4h, and then curing at 130°C for 5h;
[0111] S4, preparation of modified silicone rubber: 160g of methyl vinyl silicone rubber was put into a kneader, 50g of white carbon black, 64g of aluminum hydroxide, 8g of hydroxy silicone oil, 1.2g of diphenylsilanediol, and 1.4g of triethanolamine were added, and after mixing evenly, 40g of modified nano titanium dioxide, 30g of alumina fiber, and 1.6g of 4-methyl-6-tert-butylphenol were added, and the temperature was raised to 140°C, and the material was kneaded at -0.1MPa for 1h and discharged. The obtained rubber material was put into an open mill, and the rubber material was mixed until the rubber material was smooth, and the mixture was allowed to stand for 18h. The mixture was rolled on the open mill, 3g of diisopropylbenzene peroxide was added, and the mixture was thinned 8 times to obtain a sheet, and the modified silicone rubber was obtained after standing for 20h;
[0112] S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body;
[0113] S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding, the vulcanization molding process is divided into primary vulcanization and secondary vulcanization; the process parameters of the primary vulcanization are a vulcanization temperature of 120°C and a vulcanization time of 10 min; the process parameters of the secondary vulcanization are a vulcanization temperature of 180°C and a secondary vulcanization time of 10 min, the thickness of the modified silicone rubber on the surface of the porcelain column insulator body after vulcanization is 1 mm; a high-performance composite porcelain suspension rod insulator is obtained.
[0114] The preparation method of the modified epoxy resin in step S2 is as follows:
[0115] 20g of carbon fiber was treated with plasma and then immersed in 200mL of 1mol / L sodium hydroxide aqueous solution. The plasma treatment process was to evacuate the plasma instrument and then introduce oxygen, the power was set to 180W, and the treatment time was 8min; the immersion time was 2h, and after the immersion was completed, the carbon fiber was taken out, washed and dried to obtain the pretreated carbon fiber; 100g of carboxyl-terminated perfluoropolyether was dissolved in 500mL of N,N-dimethylformamide, 10g of 5-amino-2-fluorobenzyl alcohol and 100mL of EDC / NHS aqueous solution (the concentration of EDC in the EDC / NHS aqueous solution was 40mM / L, and the concentration of NHS was 50mM / L) were added, the pH was adjusted to 5, and the reaction was heated at 60°C for 3h. After cooling, 8g of the pretreated carbon fiber was immersed in the reaction solution, and after immersion for 1h, the carbon fiber was taken out, dried, and crushed through a 120-mesh sieve to obtain the polymer-coated carbon fiber; 12g of the polymer-coated carbon fiber was added to 65g of epoxy resin and stirred and mixed evenly to obtain the modified epoxy resin.
[0116] The preparation method of the modified titanium dioxide in step S4 is as follows:
[0117] 20 g of nano titanium dioxide was added to 200 mL of 50 wt% ethanol aqueous solution, and 2.5 g of KH550 was added. The mixture was heated at 50°C for 4 h. After the reaction was completed, the mixture was cooled and filtered. The solid was collected, washed, and added to 200 mL of dimethyl sulfoxide. A 1 mol / L NaOH aqueous solution was added to adjust the pH value to 9. 5.2 g of 5-amino-2-fluorobenzyl alcohol was added and the mixture was heated at 60°C for 2 h. After the reaction was completed, the mixture was cooled, filtered, and washed until the pH value of the filtrate was neutral, and then dried to obtain fluorinated titanium dioxide, which is the modified nano titanium dioxide.
[0118] Performance Testing
[0119] Mechanical property test of porcelain column insulator body: The porcelain column insulator bodies prepared in Examples 1-3 and Comparative Example 1 were tested for bending resistance according to GB / T8411.2-2008 "Ceramic and glass insulating materials Part 2: Test methods". The test results are shown in Table 1:
[0120] Table 1 Test results of bending resistance of high performance composite porcelain suspension rod insulator
[0121] Flexural strength(MPa) Example 1 213 Example 2 208 Example 3 226 Comparative Example 1 159
[0122] Electric breakdown strength: The high performance composite porcelain suspension rod insulators prepared in Examples 1-3 and Comparative Examples 1-3 were tested for electric breakdown strength according to the standard GB / T1408.1-2016 "Dielectric strength electrical strength test method for high performance composite porcelain suspension rod insulators Part 1". The test results are shown in Table 2:
[0123] Table 2 Test results of electrical breakdown strength of high performance composite porcelain suspension rod insulators
[0124] Electrical breakdown strength (kV / mm) Example 1 54.63 Example 2 52.32 Example 3 55.18 Comparative Example 1 42.56 Comparative Example 2 35.84 Comparative Example 3 39.25
[0125] Anti-algae performance test: The experimental culture method refers to GB / T21353-2008 "Determination of anti-algae performance of paint film" and GB / T24127-2009 "Test method for anti-algae performance of plastics". The green algae are fresh green algae. The test is carried out in a light incubator GZX-250. The temperature of the incubator is 28±2℃ and the relative humidity is 90%±5%. The standard test cycle is 21 days and the doubled test cycle is 42 days. The culture observation is shown in Table 3:
[0126] Antifouling performance test:
[0127] Sodium chloride and diatomaceous earth with a particle size of 2000 mesh were mixed evenly at a mass ratio of 1:5 by ball milling, and placed in a 120℃ oven for 30 minutes before accumulation of dirt to remove the moisture absorbed from the air to obtain the dirt. The sample mass was weighed, and the sample was placed in an artificial dirt accumulation box. The high-voltage power supply was started to put the sample in an electric field with a field strength of 0.7kV / cm. The air compressor was started to form a negative pressure, and the dirt was sucked into the artificial dirt accumulation box, blown out in a mist, and naturally settled. Each time the dirt was accumulated, the mass of the dirt was 12g. Each sample was accumulated 5 times. After turning off the high-voltage power supply, the sample was taken out, the dirt on the edge and back of the sample was wiped off, and the sample mass was weighed. The mass difference before and after the sample was accumulated was the amount of dirt. The test results are shown in Table 3:
[0128] Table 3 Test results of anti-algae and anti-fouling performance of high-performance composite porcelain suspension rod insulators
[0129] Algae resistance level Dirt accumulation (mg) Example 1 Level 0 12.6 Example 2 Level 0 13.4 Example 3 Level 0 11.8 Comparative Example 1 Level 0 15.7 Comparative Example 2 Level 2 19.2 Comparative Example 3 Level 1 16.5
[0130] It can be seen from the experimental results in Table 1 and Table 2 that the high-performance composite porcelain suspension rod insulator prepared by the present invention has excellent electrical breakdown strength and anti-algae and anti-fouling properties, can withstand a large load force, is not easily damaged, and has high insulation performance, thereby improving the safety of the insulator during use.
[0131] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A high performance composite porcelain suspension rod insulator, characterized in that: It comprises a porcelain column insulator body and modified silicone rubber coated on the surface of the porcelain column insulator body; the porcelain column insulator body comprises the following components in parts by mass: 10-25 parts of Qingyuan mud, 10-20 parts of ash clay, 8-15 parts of kiln mud, 15-25 parts of porcelain clay, 5-20 parts of bauxite, 5-15 parts of nano silicon carbide, 3-10 parts of quartz sand, 10-15 parts of modified epoxy resin, and 5-8 parts of curing agent.
2. The insulator according to claim 1, characterized in that: The preparation method of the modified epoxy resin is as follows: The carbon fiber is plasma treated and then immersed in a sodium hydroxide aqueous solution, and then taken out and dried to obtain a pretreated carbon fiber; the carboxyl-terminated perfluoropolyether is dissolved in N,N-dimethylformamide, 4-amino-3-hydroxybenzoic acid and EDC / NHS aqueous solution are added, the pH is adjusted to 4-6, heated for reaction, and the pretreated carbon fiber is immersed in the reaction solution after cooling. After the impregnation is completed, the carbon fiber is taken out, dried, crushed and sieved to obtain a polymer-coated carbon fiber; the polymer-coated carbon fiber is added to the epoxy resin and stirred to mix evenly to obtain the modified epoxy resin.
3. The insulator according to claim 2, characterized in that: The mass ratio of the carboxyl-terminated perfluoropolyether, 4-amino-3-hydroxybenzoic acid, and pretreated carbon fiber is 100:8-10:6-10; the concentration of EDC in the EDC / NHS aqueous solution is 30-40mM / L, and the concentration of NHS is 40-50mM / L; the mass ratio of the polymer-coated carbon fiber and the epoxy resin is 10-15:50-70.
4. The insulator according to claim 1, characterized in that: The curing agent is a polyamide curing agent and / or an acid anhydride curing agent.
5. A method for preparing an insulator according to any one of claims 1 to 4, characterized in that: The steps include: S1. Weigh the raw materials according to the formula, mix Qingyuan mud, ash clay, kiln mud, porcelain clay and bauxite evenly, and then put them into a ball mill to obtain a mixture; S2, wet ball milling: adding nano silicon carbide, quartz sand, and modified epoxy resin to the mixture obtained in step S1 to obtain a mixed material, adding water to perform wet ball milling to obtain a slurry; then adding a curing agent and mixing and stirring to obtain a base material; S3, green compacting: adding the base material obtained in step S2 into a mold for molding, degassing, heating and curing, cooling and demolding, and then finely grinding, cleaning, degreasing and drying the surface of the porcelain column insulator body to obtain the porcelain column insulator body; S4, preparing modified silicone rubber: putting the raw silicone rubber into a kneader, adding a structure control agent, a filler, an anti-aging agent, and an accelerator for mixing, and then adding a vulcanizing agent, thinning, and producing a sheet to obtain the modified silicone rubber; S5. Applying modified silicone rubber: evenly applying the modified silicone rubber on the surface of the porcelain column insulator body; S6. Vulcanization molding: placing the porcelain column insulator body coated with modified silicone rubber in a vulcanizer for vulcanization molding to obtain a high-performance composite porcelain suspension rod insulator.
6. The preparation method according to claim 5, characterized in that: The preparation process of the modified silicone rubber in step S4 is as follows: put methyl vinyl silicone rubber into a kneader, add white carbon black, aluminum hydroxide, hydroxy silicone oil, diphenylsilanediol, and triethanolamine, mix evenly, add alumina fiber, and 4-methyl-6-tert-butylphenol, heat to 130-150°C, knead for 1-2 hours at -0.1MPa to -0.08MPa, and discharge the material. The obtained rubber material is put into an open mill, and the mixture is kneaded to a smooth rubber material, and the mixture is allowed to stand for 18-24 hours. The mixture is rolled on the open mill, a vulcanizing agent is added, and the mixture is thinned 5-10 times to produce a sheet, and the modified silicone rubber is obtained after standing for 18-24 hours.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the methyl vinyl silicone rubber, white carbon black, aluminum hydroxide, hydroxy silicone oil, diphenylsilanediol, triethanolamine, modified nano titanium dioxide, aluminum oxide fiber, 4-methyl-6-tert-butylphenol and vulcanizing agent is 70-90:20-30:30-35:3-5:0.5-1:0.5-1:15-25:10-20:0.5-1:1-2.
8. The preparation method according to claim 7, characterized in that: The preparation method of the modified nano titanium dioxide is as follows: adding nano titanium dioxide to an ethanol aqueous solution, adding KH550, heating for reaction, cooling and filtering after the reaction is completed, collecting solids, washing, adding to dimethyl sulfoxide, adding NaOH to adjust the pH value to 8-10, adding 5-amino-2-fluorobenzyl alcohol, heating for reaction, cooling, filtering, washing until the pH value of the filtrate is neutral after the reaction is completed, and then drying to obtain fluorinated titanium dioxide; dispersing fluorinated titanium dioxide in water, adding glycidyl trimethylammonium chloride, heating for reaction, cooling after the reaction is completed, filtering, collecting solids, washing, and drying to obtain modified nano titanium dioxide.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the nano titanium dioxide, KH550, 5-amino-2-fluorobenzyl alcohol and glycidyl trimethylammonium chloride is 15-25:2-3:4-6:3-5.
10. The preparation method according to claim 5, characterized in that: The coating method in step S5 is one of spraying, brushing and dipping.
Citation Information
Patent Citations
Anti-pollution-flashover insulator
CN106243859A
Fabrication method of aluminum oxide porcelain core composite insulator
CN108305734A
Temperature-resistant insulating silicone rubber, preparation method thereof and temperature-resistant insulating adhesive tape
CN112940512A
Antifouling rod-shaped suspension porcelain insulator and preparation method thereof
CN113053594A
High-strength long-rod-shaped insulator and preparation method thereof
CN114171263A